Degree of swallowing impairment in the elderly: clinical and instrumental assessment - Salgado, Tatiane Totta; Oliveira, Cris Magna dos Santos; Gatti, Marina; Silva, Roberta Gonçalves da [UNESP]; Honório, Heitor Marques; Berretin-Felix, Giédre (Elsevier, 2024)
Objective: To classifying the degree of swallowing impairment in the elderly, comparing clinical and instrumental assessment. Methods: This is a cross-sectional study with quantitative and qualitative analysis of clinical and instrumental assessment of 37 elderly, aged 60–82 years, of both genders without neurological, oncological or systemic diseases, participated in this study. All participants were submitted to clinical evaluation and their results compared through fiberoptic endoscopic evaluation of swallowing considering liquid, pudding and solid food consistencies. Data were analyzed descriptively and statistically using the analysis of variance test (two-way ANOVA) and Tukey's post hoc test (p < 0.05). Results: In the clinical evaluation there was a higher occurrence of moderate swallowing impairment, followed by functional swallowing, while in fiberoptic endoscopic evaluation of swallowing the severity of the impairment was greater for moderate and mild degrees. There was no statistical difference between the clinical and instrumental evaluation methods. However, there was a significant interaction between the variables, with a difference for liquid consistency in the instrumental evaluation method. Conclusion: Healthy elderly have different degree of swallowing impairment according to food consistency. The clinical assessment using a scale that considers the physiological changes of the elderly, presented results similar to those found in the instrumental examination. Level of Evidence: 2.
Keywords: Aged; Clinical protocols; Deglutition; Digestive system; Endoscopy